Toward a History of Canadian Departments of Anthropology: Retrospect, Prospect and Common Cause - Darnell, Regna (Anthropologica, 2022)
This article presents a framework for documenting the institutional history of Canadian anthropology through the diverse experiences of the departments in which anthropology is taught. The historical baseline is the debate over whether or not Canada has a distinct national tradition in anthropology and, if so, what is its character. Early anthropologists in Canada are noted, with attention to their roles in the emergence of an institutional framework of professional organizations, publication outlets, professional training and employment opportunities. The present configuration of Canadian departments is discussed in terms of affiliations to related disciplines, degree programs offered and number of students enrolled in them, subdisciplinary specializations of faculty, professional age of faculty, emeritus faculty (our tribal elders) and country of highest degree of Canadian faculty. The next step in documenting the history of Canadian anthropology is to produce more qualitative participant-observation histories of particular departments across the country; there is some urgency as the founders of these departments reach the end of their careers. Given the financial exigencies now facing Canadian academic life, there seems some further urgency in documenting the existence of a distinguished anthropological tradition in Canada.